“There is just too much going on there”: Nonverbal communication experiences of autistic adults - Holly Radford; Bronte Reidinger; Steven K. Kapp; Ashley de Marchena (PLoS ONE, 2025)
Background Atypical nonverbal communication is required for a diagnosis of autism, yet little is known about how autistic adults use gestures, facial expressions, and other nonverbal behaviours in social interactions, especially from autistic adults’ perspectives. The objectives of this study were to understand: (1) autistic adults’ experiences of using nonverbal communication in interactions, (2) how nonverbal communication impacts autistic people’s lives, and (3) how autistic adults manage nonverbal communication differences. Methods 27 threads from the internet discussion forum wrongplanet.net, all containing dialogue focused on nonverbal communication, were subjected to qualitative analysis. Inductive and deductive coding were used to identify excerpts relevant to miscommunication experiences, communication strengths, and compensatory strategies. A total of 362 excerpts were coded (kappa = .79). Coded excerpts were then extracted and examined for themes, using member checking. Results Major themes included: (1) Cognitive differences resulting in autistic adults requiring more time and energy to manage nonverbal communication in interactions; (2) Miscommunication related to nonverbal communication is bilateral; (3) Nonverbal communication differences can negatively impact the lives and wellbeing of autistic adults; (4) autistic adults use a range of skills and strategies to manage nonverbal communication; and (5) Autistic adults demonstrate variability in the production and interpretation of nonverbal cues. Conclusion Several of our themes, including mutual miscommunication and negative impacts of atypical communication, are consistent with previous qualitative work on communication experiences of autistic adults. The current findings provide new insight into the internal and external factors influencing the nonverbal communication experiences of autistic adults, in particular the cognitive processes involved. We advocate for solutions that shift the responsibility for effective communication onto all members of society. For example, sharing and accepting preferred communication modalities, and checking in about whether a message was received correctly instead of making assumptions.